Study of Heat Transfer behavior of Chilled Ready to Eat Foods and Food Spoilage Characteristic after Microwave Heating Process - Klinbun, Waraporn; Liamkaew, Ruamporn (Burapha Science Journal, 2026)
This research aims to study heat transfer phenomena and food spoilage in chilled food heating process subjected to microwave energy. Two chilled food products from 7-Eleven shop as: sweet mung bean porridge with taro coconut cream and steamed egg custard were chosen as experimental samples. The experiment of ready to eat food heating using a microwave oven with 2,450 MHz and 1,300 watts was performed. During the experiment, the temperatures of the sample have been recorded by reading from fiber-optic probes and infrared camera. The study of food spoilage after heating considered in terms of microbial analysis and sensory characteristics as perceived by sight, smell and touch. From the results, the temperature profile of both samples is same distribution. The temperature at the edge is higher than that of the center temperature of the food. In part of food spoilage, it was found that the total amount of microorganisms detected in food will increase in number and increases in quantity when left over at room temperature for a longer period. For foodborne pathogen, Samonella spp. was not detectable (ND) during this period (48 hours). In addition, the food was stretchy slime with a fermented odor, which was classified as an off-flavor after 8 hours left at room temperature (25 oC). The results of this study can be used as a guideline for the development of product pattern and label indications.